Adsorption Kinetics of Fe and Mn with Using Fly Ash from PT Semen Baturaja in Acid Mine Drainage - Indah Purnamasari; Endang Supraptiah (Indonesian Journal of Environmental Management and Sustainability, 2017)
One used method to reduce heavy metal ions in acid mine drainage is to adsorb them by coal fly ash. This research aimed to study the isotherms equilibrium and the adsorpstion kinetics that fit with decreasing metals ion. Acid mine draigane and fly ash were charge into batch coloumn adsorption with specified comparison. Variables investigated were dactivated and activated fly ash, adsorption times (0, 20, 30, 40,50, and 60 minutes), adsorben weights (10, 20, 30, 40, 50, and 60 gram), and pH (1, 3, 5, 7, and 9). The results showed that fly ash can be used to reduce the levels of heavy metal ions Fe and Mn. Coal fly ash adsorption model of acid mine drainage fits to Freundlich adsorption isotherm in all condition. First order pseudo model kinetics is suitable for Fe and Mn adsorption processes. The value of adsorpsi rate constants vary around : Fe and Mn (deactivated fly ash) 0.2388 min-1 with R2 = 0.4455 and 0.4173 min-1 with R2 = 0.9781, Fe and Mn (activated fly ash) 0.5043 min-1 dengan R2 = 1 and 0.2027 min-1 with R2 = 0.8803.